2021
DOI: 10.1021/acsomega.1c04635
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Bending Reveals Simultaneous Enhancements of Strength and Ductility of Cortical and Cancellous Layers Induced by the Cartilage Layer

Abstract: The energy absorption and toughening effect of cartilage could effectively protect bone from damage, and the enhancement mechanisms of cartilage on deformation resistance or strength need to be revealed. Using a self-developed in situ bending tester integrated with an optical microscope, in situ bending of the composite bone structure consisting of the cartilage layer and cortical and cancellous layers was carried out, accompanied by simultaneously obtained continuous morphological changes in diverse deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…13,14 In order to further analyze the differences in the structure, composition, and mechanical characteristics of AC, we have previously conducted studies on the mechanical properties of the whole cartilage surface and the in situ three-point bending test of the composite structure in cartilage. 15,16 The purpose of this experiment was to study the creep properties and morphological characteristics of the entire knee joint cartilage, and to record the surface morphology changes and internal composition structure. To this end, we recently used nanoindentation experiments to compare the creep properties of four regions in normal porcine knee cartilage, and determined the global creep properties of AC using five-point sampling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 In order to further analyze the differences in the structure, composition, and mechanical characteristics of AC, we have previously conducted studies on the mechanical properties of the whole cartilage surface and the in situ three-point bending test of the composite structure in cartilage. 15,16 The purpose of this experiment was to study the creep properties and morphological characteristics of the entire knee joint cartilage, and to record the surface morphology changes and internal composition structure. To this end, we recently used nanoindentation experiments to compare the creep properties of four regions in normal porcine knee cartilage, and determined the global creep properties of AC using five-point sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Athanasiou et al found that the posterior cartilage of the medial femoral condyle was harder than the posterior cartilage of the lateral femoral condyle. , Appleyard′s study discovered that the AC under the meniscus of the sheep knee joint was 200% to 500% harder than the uncovered area . The ability of AC to perform its functions depends on its main components, unique structural and biomechanical properties. , In order to further analyze the differences in the structure, composition, and mechanical characteristics of AC, we have previously conducted studies on the mechanical properties of the whole cartilage surface and the in situ three-point bending test of the composite structure in cartilage. , The purpose of this experiment was to study the creep properties and morphological characteristics of the entire knee joint cartilage, and to record the surface morphology changes and internal composition structure. To this end, we recently used nanoindentation experiments to compare the creep properties of four regions in normal porcine knee cartilage, and determined the global creep properties of AC using five-point sampling.…”
Section: Introductionmentioning
confidence: 99%